Relationship between blood group and risk of infection, intubation and death in Covid pandemic - Renu Singh; M Siddiqui (Tropical Journal of Pathology and Microbiology, 2022)
Background: Few people infected by the coronavirus become seriously ill, while others show mild symptoms or are asymptomatic. Recent research points out that the ABO blood group might play an essential role in a person’s susceptibility and severity of COVID-19 infection. Aims: This study is conducted to find the relationship between ABO groups and COVID-19 infection. Methods: A total of 395 patients were included in this study. The study population was divided based on ABO blood groups into types A+, A−, B+, B −, AB, O+, and O−. Results: Blood group B was associated with high susceptibility to infection. We found slightly increased infection prevalence among the Rh factor positive blood group. The risk of infection was decreased among blood groups with Rh factor negative. Cases having blood group B have higher chances of covid-19 infection followed by AB and type O. Conclusion: We estimated Rh-negative blood types to have a protective effect for covid -19 infection. Our results add to the growing body of evidence suggesting blood group type may play a role in COVID-19 infection.